An Examination of the Niche-strategy Content and Structure of the Small Firms in the Hospitality Industry: The Impact on Niche-strategy Organizational Performance - Maleewat, Nitirat; Banjongprasert, Jantima (Journal of Business, Innovation and Sustainability (JBIS), 2023)
A niche marketing strategy is one of competitive strategies used to compete with other businesses in the same sector. Numerous businesses invest considerable time and effort in formulating strategies. Their initiatives, however, fail to materialize during the execution phase. Strategy execution has a high failure rate so that it is vital to address this management difficulty. According to prior studies, the content of a niche strategy and the organizational structure of a niche business are critical elements in strategy execution and it was a gap that this research aims to fulfil. A self-administered questionnaire was used to collect the data from the sample of 405 respondents including individuals who work in niche-oriented hospitality businesses in Thailand (hotels, restaurants, travel agency companies, and spa enterprises) because hospitality industry is an important industry which generate a lot of income for Thailand but it has a limit of information about niche strategy implementation for this industry. Structural equation modeling (SEM) is used to analyze the data. The results indicate that the content of niche strategy and the structure of niche oriented firms have positive effects on organizational performance. Moreover, human resource management fully mediates the association between the niche strategy's content and the structure of niche-oriented corporations to organizational performance. This study contributes to the strategic management and hospitality sector by demonstrating that niche strategy firms should prioritize the content of their niche strategy, their niche oriented firm structure, and human resource management in order to enhance their performance.